Impact of Equity Investment Intention Towards Behaviour: An Empirical Analysis. Issue 3 (June 2023) - Srivastava, Shelly; Roy, Supriyo
Investments made by investors contribute to both inflow and outflow of funds in the capital market. Investment decision making is complex due to its uncertain behaviour. In literature, there is evidence of a gap between intention and behaviour among other aspects of human behaviour like consumer buying behaviour. Therefore, this study explores the intention–behaviour gap in investment behaviour of retail investors by examining the effect of two moderators, namely risk propensity (RP) and opinion of stakeholders (OPI). The present study also focuses on identifying financial and non-financial factors influencing equity investment intention (EII) and measures its impact on equity investment behaviour (EIB). A model is, thus, conceptualized and hypotheses have been developed accordingly. For validation of the model, a set of primary data of retail investors is collected (through questionnaire framing) and the hypotheses are tested by using advanced statistical techniques, namely structural equation modelling. The outcomes of this study signify the impact of EII that catapults behavioural approach in investment decision making for any potential investor in the near future.